Which Fat Processing Can Achieve Optimal Transplantation in Patients With Insufficient Fat Resource?. Issue 4 (October 2019) - Kang, Deni; Fu, Su; Luan, Jie
Abstract : Background: Autologous fat transfer has been widely used in breast augment surgery. The breast fat graft is different form facial, it needs megavolume grafts. However, most Asian women are thin, who often encounter the fat resource insufficiency during breast augmentation. In fact, some processing methods do contribute to great loss of potential fat that could have been grafted. How to choose a best processing method to achieve optimal transfer in patients with insufficient fat resources is fairly important. Methods: Lipoaspirate was obtained from 10 healthy female patients who underwent liposuction from abdomen. According to the processing methods, 10-mL initial fat grafts divided into 4 groups: decantation (group A), centrifugation (group B), cotton pad (group C), and cell-assisted lipotransfer (CAL) (group D). Lipoaspirate from each group was compared in the vitro and vivo experiments. The content and function of stromal vascular fraction (SVF) were compared as well as lipoaspirate survival after grafting in nude mice. Results: The SVFs were counted in decantation group 4.32 ± 0.75 × 10 6 /mL, centrifuge group 3.48 ± 0.78 × 10 6 /mL, cotton pad group 1.64 ± 0.84 × 10 6 /mL, CAL group 4.08 ± 0.73 × 10 6 /mL. The decantation group was higher than the cotton pad group ( P < 0.05). All the groups' SVFs had capability of multilineage differentiation. The fat graft weight in decantation group: 0.3908 ± 0.023 g, centrifuge group 0.3073 ± 0.015 g, cotton pad group 0.1726 ± 0.019 g, and CAL group 0.2396 ± 0.021 g. The weight of the fat graft in the decantation group was greater than that of the centrifugation group, cotton pad group and CAL group ( P < 0.05). There was no significant difference in cell integrity, necrotic cysts and fibrosis between the groups. The vascularization degree in the cotton pad group was lower than that in the decantation group ( P < 0.05). Conclusions: Decantation processing can achieve optimal transplantation in patients who have insufficient fat resources.